Karakteristik Virtual Opinion Leader dalam Grup Whatsapp Uber Condet Bersatu - Wardhono, Dwi Cahyo Utomo (Magister of Communication Science, Sahid University Jakarta., 2021)
This study aims to describe more deeply the characteristics of a virtual opinion leader in the whatsapp group. The theory used in this study is Computer Mediated Communication (CMC). WhatsApp group admin is an opinion leader in cyberspace (online) where his opinion can determine the formation of opinions of group members or followers to take further action in the real world (offline) and as if the group members are powerless to reject information or opinions that have been submitted by group admins. The results of this study indicate that there are several characteristics of offline opinion leaders that have no effect or are different from the characteristics of online opinion leaders. Among these are the level of education and the level of socio-economic status that is higher than the other members. In the online world, the level of participation and creativity is prioritized as the characteristics of a virtual opinion leader, because these two things can reflect an ideal virtual opinion leader.